Inovasi Pembelajaran IPS dengan Implementasi Metode Field Trip - Dhi Bramasta; Sutomo Sutomo; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2022)
The development of science and technology demands adjustments in the social science learning process, so that the learning carried out can always adapt to existing developments. So innovation is needed in the form of development, discovery, combination, improvement in the learning process, one of which is the implementation of the field trip method. However, Social Science learning innovations with The field trip method in learning is still relatively fixated on the steps of the field trip method and has not shown the form of innovation. Research objectives for knowing how to innovate Social Science learning by implementing the field trip method. So it can be seen how the field trip method in improving the quality of learning Social Sciences. This study applies a literature study by reviewing 14 literatures. The results showed that the research conducted related to the field trip method in Social Science learning is still dominated by quantitative and classroom action research methods. For qualitative it is still relatively small. Then the relevant literature study method is applied to find gaps in getting ideas for combining, creating, updating or developing the implementation of the field trip method in Social Science learning. Learning with the implementation of the field trip method in Social Science learning, would be better if it did not only focus on learning outcomes. But also pay attention to the learning process, where the packaging of the field trip method can be combined with other methods or ways so that learning can be more interesting, meaningful and increase students' motivation and interest in learning. So automatically learning outcomes will increase.